Evaluation of an ozone generation system for the control of microorganisms in the indoor air of sanitary environments - Yali–Rivera, Judith (2022)
Objetive: Evaluate an Ozone Generating System (OGS) through of the microorganisms count and identificated in the air of the sanitary environments of the National Institute of Health (INS) from Peru. The study: These were exposed to OGS for 1 min per m2, air samples were collected at volumes of 200L, 500L and 1000L by impaction, pre and post exposure to OGS, cultures were obtained on Plate Count Agar (PCA) and Oxytetracycline Glucose Agar (OGA) grown at 35°C±2°C for 48 hours and 25°C ± 2°C for 5 days. Findings: A decrease in the count of fungi after exposure to OGS, the difference being statistically significant for the volumes of 200L (p=0.047) and 1000 L (p<0.005); Aspergillus spp. species were identified in most cultures, in bacteria no significant difference was observed. Conclusions: The OGS is a method that inhibits the growth of most fungi in sanitary environments.